Perioperative anemia - N. O. Khovasova (Медицинский совет, 2021)
Over 10 million operations are performed each year in Russia. A successful surgical treatment demands assessment and mitigation of perioperative risks, one of which is anemia. Patients with low hemoglobin are at greater risk of developing complications and adverse outcomes. These patients more often stay longer at hospitals, have more in-hospital events and readmissions.Perioperative anemia may be present before surgery, low hemoglobin levels can result from surgery, and can persist after hospital discharge. Preoperative anemia is associated with inferior surgical outcomes and is also an independent risk factor for perioperative complications (acute kidney injury, infectious, thromboembolic, cardiovascular events) and death. Postoperative anemia impairs recovery and increases the risk of reoperations and readmissions.Absolute and functional iron deficiency is the most common cause of anemia in the perioperative period. The prescription of iron supplements is indicated in the presence of iron deficiency. If the operation is scheduled to be performed in 6 weeks and longer, the prescription of oral iron forms is recommended. If less than 6 weeks remain before surgery, parenteral iron therapy is prescribed. If hemoglobin levels increase insignificantly during such therapy, high-dose iron supplements are indicated. When it comes to emergency surgery and the anemia is not severe, it is recommended to intravenously administer high-dose iron supplements immediately before surgery. In case of severe anemia, blood transfusion is indicated. According to the patient’s blood management concept, blood transfusion should be minimized, including due to the use of high-dose iron supplements, one of which is ferric carboxymaltose.The choice of treatment for anemia in the postoperative period depends on its severity, the patient’s comorbidities, the type of surgery and the presence of surgical events. In most cases, early intravenous iron therapy is recommended, giving priority to single administration of high-dose iron supplements. Blood transfusion is indicated to patients who have severe anemia, are actively bleeding, and to patients with a severe anemia after the bleeding has been stopped. Iron therapy continues at the outpatient stage of treatment for a long time until the hemoglobin and ferritin levels are normalized, reflecting the replenishment of iron stores in the depot organs.